An integrated analysis on source-exposure risk of heavy metals in agricultural soils near intense electronic waste recycling activities. (December 2019) - Yang, Shiyan; He, Mingjiang; Zhi, Yuyou; Chang, Scott X.; Gu, Baojing; Liu, Xingmei; Xu, Jianming
Graphical abstract: Highlights: An intergraded source-exposure risk approach was developed. Interrelationships among source, sink and human health were assessed. Parent material and agrochemical application caused the highest non-cancer risk. Industrial activities caused the highest total cancer risk. Reducing industrial discharge and agrochemical use is key for alleviating human health risk. Abstract: Conducting integrated analysis of the source, exposure and health risk of heavy metals is critical for developing mitigation strategies of soil contamination. Taking the former electronic waste (e-waste) dismantling center in China as an example this study quantitatively apportioned source contribution of soil heavy metals in this area by statistical analysis and positive matrix factorization (PMF) model. Furthermore, the human health risk of identified sources were quantified by combining source profiles and exposure risk assessment. The seven heavy metals investigated were arsenic (As), cadmium (Cd), copper (Cu), chromium (Cr), nickel (Ni), lead (Pb) and Zinc (Zn). Results indicated that agricultural soils were mainly contaminated with Cd and Cu. Parent material and pesticide, fertilizer application, industrial discharge, and vehicle emission accounted for 46.6, 22.2, and 31.2%, respectively, of the accumulation of metals in the soil. Moreover, these sources contributed 52.9, 19.0, and 28.1%, respectively of the total non-cancer risk. For the total cancer risk, the contribution of these three sources was 39.2, 45.3, and 15.5%, respectively. Despite that industrial discharge contributed the least to the accumulation of metals (22.2%), it contributed the most to the total cancer risk (45.3%). Reducing industrial emission was crucial for minimizing the heavy metal input to agricultural soils and preventing potential health hazard. These findings could provide support for environmental protection authority to improve the management and risk prevention of contaminated farmland.